2001
DOI: 10.1111/j.1469-7793.2001.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

ACh‐induced rebound stimulation of L‐type Ca2+ current in guinea‐pig ventricular myocytes, mediated by Gβγ‐dependent activation of adenylyl cyclase

Abstract: The effects that muscarinic receptor stimulation have on the cAMP‐dependent regulation of L‐type Ca2+ currents were studied in isolated guinea‐pig ventricular myocytes using the whole‐cell configuration of the patch‐clamp technique. The muscarinic agonist ACh inhibited the Ca2+ current stimulated by the β‐adrenergic agonist isoprenaline (Iso), and washout of ACh revealed a stimulatory response that appeared as a transient rebound increase in the amplitude of the Ca2+ current. The ACh‐induced stimulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 50 publications
5
45
0
Order By: Relevance
“…3C), as described previously for cardiac myocytes (14,37). Therefore, it can be concluded that G i/o proteins mediate this effect.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…3C), as described previously for cardiac myocytes (14,37). Therefore, it can be concluded that G i/o proteins mediate this effect.…”
Section: Discussionsupporting
confidence: 73%
“…To measure real-time dynamics of the well-described cAMP rebound phenomenon after withdrawal of muscarinic stimulation (14,16,37), we chose atrial myocytes, because overall they show more responsiveness to muscarinic receptor stimulation than do ventricular myocytes (38). We therefore acutely isolated atrial myocytes from transgenic mice expressing the well-established cAMP biosensor Epac1-camps (35) and imaged cAMP levels by means of FRET.…”
Section: Muscarinic Receptor-mediated Camp Rebound Response In Cardiamentioning
confidence: 99%
See 2 more Smart Citations
“…Cholera toxin activates G S via a receptor-independent mechanism (Belevych et al, 2001). Treatment with 1 g/ml cholera toxin failed to induce AA release (Fig.…”
Section: Resultsmentioning
confidence: 99%